The Paradox of Church and Wood : Selected Writings of H. Richard Niebuhr - Diefenthaler, Jon (Book collections on Project MUSE., 2015)
"In this volume, Jon Diefenthaler collects for the first time over forty writings that trace the lineage of Niebuhr's thought, presents them in a single place, and makes a case for their enduring value in a postchurch religious environment. The volume is a treasury of little-known and hard-to-find pieces, making scholarship and understanding easier."--back cover.